2022
DOI: 10.1038/s41598-022-08510-8
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state theta activity is linked to information content-specific coding levels during response inhibition

Abstract: The neurophysiological processes underlying the inhibition of impulsive responses have been studied extensively. While also the role of theta oscillations during response inhibition is well examined, the relevance of resting-state theta activity for inhibitory control processes is largely unknown. We test the hypothesis that there are specific relationships between resting-state theta activity and sensory/motor coding levels during response inhibition using EEG methods. We show that resting theta activity is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…No such effects were found in the groups of participants required to train the modulation of both these frequency bands simultaneously. Overall, these findings support existing knowledge (Pscherer et al, 2019 , 2020 , 2022 ) showing that resting state power carries a different functional relevance than it is the case for task-related oscillatory power and outcomes measured on the behavioural level. This further strongly depends on age and the cognitive function in question (Pscherer et al, 2019 , 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…No such effects were found in the groups of participants required to train the modulation of both these frequency bands simultaneously. Overall, these findings support existing knowledge (Pscherer et al, 2019 , 2020 , 2022 ) showing that resting state power carries a different functional relevance than it is the case for task-related oscillatory power and outcomes measured on the behavioural level. This further strongly depends on age and the cognitive function in question (Pscherer et al, 2019 , 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, parietal afferents terminate in the midcingulate cortex (Vogt, 2016 ). Since the parietal cortex has been related to perceptual processes (Bodmer & Beste, 2017 ; Santangelo et al, 2015 ) and input integration (Gottlieb, 2007 ; Gottlieb & Snyder, 2010 ; Pscherer et al, 2022 ), the activation in the midcingulate cortex could also reflect theta band‐related perception‐action integration processes. The suggested functional role of perception‐action integration is underpinned by the finding that dynamic representations of goal‐directed actions are encoded in the midcingulate cortex (Holroyd et al, 2018 ; Vogt, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly the case for oscillatory brain activity, and thus, a significant property of neural information processing (Buzsáki, 2006 ; Herrmann et al, 2016 ; Siegel et al, 2012 ; Ward, 2003 ). So far, increased theta activity accompanying successful response inhibition has been shown frequently (Chmielewski et al, 2016 ; Dippel et al, 2016 , 2017 ; Huster et al, 2013 ; Liu et al, 2014 ; Müller et al, 2017 ; Pscherer et al, 2019 , 2021 , 2022 ; Vahid et al, 2018 ) and has been related to activation differences in the superior and medial frontal gyrus, the supplemental motor area (Dippel et al, 2017 ; Pscherer et al, 2019 , 2021 ), as well as the temporo‐parietal junction (Dippel et al, 2016 ). Furthermore, when information is conflicting and increases the need for cognitive (inhibitory) control, medial frontal theta activity is elevated (Cavanagh & Frank, 2014 ; Cohen, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…From a biophysical view, theta oscillations are key to establishing cognitive control as they allow to coordinate neuronal activity in complex neuronal networks ( Cavanagh and Frank, 2014 ) and have repeatedly been shown to be differentially modulated by cognitive control demands, including those assessed in the current study ( Zink et al., 2018 ; Bensmann et al., 2019 ; Wendiggensen et al., 2022 ). Besides, TBA is functionally associated with conflict monitoring ( Cohen and Donner, 2013 ; Wang et al., 2014 ) and the response conflict during inhibitory control (e. g., Dippel et al., 2017 ; Wendiggensen et al., 2022 ; Pscherer et al., 2022 ). Earlier studies employing the Simon NoGo task revealed control-relevant S-R codes in TBA, especially in mid-frontal and occipital regions ( Mückschel et al., 2017 ; Yu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%